Servant Leadership: Empowering Others and Creating a Culture of Collaboration and Growth - Muktamar, Ahmad; Nurnaningsih , Nurnaningsih A (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research presents the results of a systematic literature review aimed at exploring the impact of applying service leadership concepts in the context of a highly competitive industry. The research background includes an in-depth understanding of service leadership, organizational culture, and employee behavior in an effort to create a productive and growth-oriented work environment. The research method involves searching and analyzing articles from reputable international databases using relevant keywords. The results of the discussion show that the application of the service leadership concept has a positive impact on employee motivation, job satisfaction, employee behavior and organizational culture in a highly competitive industry. The implication of this research is that it is important for organizations to adopt service leadership principles in their managerial practices in order to improve their performance and competitiveness in a dynamic business environment.